Does resistance training make a difference to the quality of life or heart health for older adults compared to aerobic exercise? A systematic review protocol from The People’s Review - Éle Quinn; Laura Bosner; Patricia Logullo; Kevin Murray; KM. Saif-Ur-Rahman; Charlene Young; Derek Stewart; Maureen Smith; Jeremy Holt; Shaun Treweek; Chris Noone; David Moher; et al. (PLoS ONE, 2026)
Background Systematic reviews bring together all the evidence on a health topic in an organised and careful way. The People’s Review aims to help the public understand what systematic reviews are and why they matter by designing and conducting their own systematic review. The question chosen for The People’s Review is: Does resistance training make a difference to quality of life and/or heart health for older adults compared to aerobic exercise? This paper outlines how we will carry out this review. Methods This is a systematic review involving the public throughout. This review will search for, include and summarise: randomised controlled trials, with older adults (50 + years), that compare resistance training (such as lifting weights) with aerobic exercise (such as walking or running), and measure quality of life or heart health. First, the technical team will search research databases to find possible studies. The public will look at summaries of these to find studies that might be relevant. Then, two members of the technical team will read the full studies and decide which ones to include. Next, the public will help collect some of the key information from the included studies. The technical team will record the rest. The public and the technical team will work together to check for biases (or flaws in how the studies were done) in the studies. Finally, if possible, the team will combine the study results using a method called meta-analysis (a way of pooling numbers together). If we can’t combine the numbers, we will write a summary of what the studies found Discussion This review will summarise all the available evidence that addresses the review question. This review could support the public to make decisions about what type of exercise to engage in as they age, and influence exercise guidelines, clinical practice and future research.